Rosetta Lander – Landing and operations on comet 67P/Churyumov–Gerasimenko. (August 2016) - Ulamec, Stephan; Fantinati, Cinzia; Maibaum, Michael; Geurts, Koen; Biele, Jens; Jansen, Sven; Küchemann, Oliver; Cozzoni, Barbara; Finke, Felix; Lommatsch, Valentina; Moussi-Soffys, Aurelie; Delmas, Cedric; et al.
Abstract: The Rosetta Lander Philae is part of the ESA Rosetta Mission which reached comet 67P/Churyumov–Gerasimenko after a 10 year cruise in August 2014. Since then, Rosetta has been studying both its nucleus and coma with instruments aboard the Orbiter. On November 12th, 2014 the Lander, Philae, was successfully delivered to the surface of the comet and operated for approximately 64 h after separation from the mother spacecraft. Since the active cold gas system aboard the Lander as well as the anchoring harpoons did not work, Philae bounced after the first touch-down at the planned landing site "Agilkia". At the final landing site, "Abydos", a modified First Scientific Sequence was performed. Due to the unexpectedly low illumination conditions and a lack of anchoring the sequence had to be adapted in order to minimize risk and maximize the scientific output. All ten instruments could be activated at least once, before Philae went into hibernation. In June 2015, the Lander contacted Rosetta again having survived successfully a long hibernation phase. This paper describes the Lander operations around separation, during descent and on the surface of the comet. We also address the partly successful attempts to re-establish contact with the Lander in June/July, when the internal temperature & power received were sufficient for Philae to become active again. Highlights: We give an overview of the Rosetta Lander activities around landing and on the comet. Separation-Descent-Landing, First Scientific Sequence and wake up are discussed. The paper focusses on the activities at the Lander Control Centre, LCC.